A Generational Divide in the Polish Academic Profession. A Mixed Quantitative and Qualitative Approach - Kwiek, Marek (My University, 2017)
In a recently changing Polish academic environment – following the large-scale higher education reforms of 2009–2012 – different academic generations have to cope with different challenges. Polish academics have been strongly divided generationally, not only in terms of what they think and how they work but also in terms of what is academically expected from them following the reforms. This article explores intra-national cross-generational differences based on a combination of quantitative (surveys, N = 3704) and qualitative (interviews, N = 60) primary empirical evidence used according to the mixed-methods approach methodology and its ‘sequential’ research design. This article explores the major dimensions of the intergenerational divide between younger and older academic generations (and how they are related to both post-1989 developments and recent reforms). It shows the power of research at a micro-level of individuals, complementing the traditional research at aggregated institutional and national levels. Implications for Central European systems are shown.
Keywords: Academic generations; European universities; Poland; generational conflicts; university governance; internationalization in research; Polish higher education; young scientists; generational approach; academic cohorts; cohort approach; teaching and research; academic roles; working time distribution; micro-level study; individual scientists